COMPARATIVE MORPHOLOGY AND IDENTIFICATION OF EGG CAPSULES OF SKATE SPECIES OF THE GENERA Atlantoraja MENNI, 1972, Rioraja WHITLEY, 1939 AND Sympterygia MÜLLER & HENLE, 1837 - Oddone, María Cristina; Vooren, Carolus Maria (Arquivos de Ciências do Mar, 2008)
A comparative study of the morphology of the egg capsule for six species of skates endemic to the southwestern Atlantic Ocean was carried out through literature review and analysis of new data. Egg capsules of Sympterygia acuta and S. bonapartii differ from those of genera Atlantoraja and Rioraja by their elongated, tendril-like posterior horns and their flat lateral margins. Egg capsules of the two Sympterygia species that occurring in the area in question differ from each other in size. In lateral view the egg capsule of Rioraja agassizi has convex ventral and dorsal faces, whereas in the three species of Atlantoraja the ventral face is flat. Within the genus Atlantoraja the most important taxonomical features for the identification of the capsules are the surface texture, the morphology of the velum and the capsule dimensions. The presence and location of attachment fibres is also an important character for capsules identification. Based on the aforementioned identification characteristics, a key to species for egg capsules of the six species is presented.